2019
DOI: 10.3389/fphar.2019.01479
|View full text |Cite
|
Sign up to set email alerts
|

The Contrasting Role of Extracellular Vesicles in Vascular Inflammation and Tissue Repair

Abstract: Extracellular vesicles are a heterogeneous family of vesicles, generated from different subcellular compartments and released into the extracellular space. Composed of a lipid bilayer encompassing both soluble cytosolic material and nuclear components, these organelles have been recently described as novel regulators of intercellular communication between adjacent and remote cells. Due to their diversified composition and biological content, they portray specific signatures of cellular activation and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 237 publications
(275 reference statements)
2
69
0
1
Order By: Relevance
“…EVs act as mediators of cell-cell communication via transporting protein, lipid, and nucleic acid cargos that are important for maintaining proper cell and organ homeostasis. EVs contribute to regulation of inflammation, tissue repair, and regeneration processes ( 31 ). How this goes awry in pathological conditions like cardiovascular calcification leading to changes in EV cargos and aggregation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…EVs act as mediators of cell-cell communication via transporting protein, lipid, and nucleic acid cargos that are important for maintaining proper cell and organ homeostasis. EVs contribute to regulation of inflammation, tissue repair, and regeneration processes ( 31 ). How this goes awry in pathological conditions like cardiovascular calcification leading to changes in EV cargos and aggregation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…When circulating EVs encounter endothelial cells, they can affect their behavior, either through interactions at the cell surface or by transfer of contents (including proteins, lipids, DNA, mRNA, and microRNAs) carrying signals from their cell of origin. Therefore, EVs (particularly exosomes, which contain nucleic acids) are thought to play a role in regulating endothelial responses to damage (Ridger et al, 2017;Oggero et al, 2019).…”
Section: Different Kinds Of Extracellular Vesiclesmentioning
confidence: 99%
“…On the other hand, Nanou et al revealed that leukocytes are also able to release L-EVs [ 54 ]. Although the authors did not prove any evidence on their possible function, other studies demonstrated that leucocyte-derived EVs play an important role in the regulation of the leukocyte-endothelial interaction [ 55 ], thus suggesting a possible implication in tumor progression by favoring cancer cell intravasation and dissemination to metastatic sites.…”
Section: Role Of L-evs In Cancermentioning
confidence: 98%